In situ TEM observing structural transitions of MoS2 upon sodium insertion and extraction. Issue 98 (7th October 2016) - Zhang, Liqiang; Tang, Yushu; Wang, Yuecun; Duan, Yongli; Xie, Degang; Wu, Chunyang; Cui, Lishan; Li, Yongfeng; Ning, Xiaohui; Shan, Zhiwei
Abstract : The sodiation and desodiation process of MoS2 was characterized by in situ TEM technique. The structural evolutions of MoS2, especially its phase transition from 2H to 1T-MoS2 and the occupancy of the Na ions during the intercalation are recognized. Abstract : In this study, the sodiation and desodiation processes of MoS2 were characterized by using an in situ TEM technique. The structural evolution of MoS2 and its performance in a coin-type cell are recognized. Our findings provide a fundamental understanding of the reaction mechanism of MoS2 as anode for Na ion batteries.